Contemporary global movement of emerging plant diseases - Bandyopadhyay, Ranajit; Frederiksen, R.A. (2000)
Plant diseases are a significant constraint to agricultural productivity. Exotic plant diseases pose a continued threat to profitable agriculture in the United States. The extent of this threat has increased dramatically in the 1980s and 1990s due to the expansion of international trade in agricultural products and frequent movement of massive volume of people and goods across national boundaries. Introduction of new diseases has not only caused farm losses, but has also diminished export revenue since phytosanitary issues are linked to international commerce. Plant pathogens and their vectors have also moved across national boundaries, sometimes naturally and at other times influenced by the recent changes in trade practices. Sorghum ergot, Karnal bunt of wheat, potato late blight, and citrus tristeza are some of the most recent examples of enhanced importance of diseases due to the introduction of plant pathogens or vectors.